Letter detector of mailbox by using solar cell technology / Basyirah Mohamed Akharan & Nur Amirah Roslan - Mohamed Akharan, Basyirah; Roslan, Nur Amirah (2015)
This project is mainly to investigate more on solar panel. Solar panel is a photovoltaic cell that converts light energy from the sun to electrical energy. Solar panel has been used widely in the world and the applications of it have been increasing day by day. Nowadays, people invest more on solar panel technology as it is more practical and environmental friendly. Therefore, solar panel is added to this letter detector of mailbox project to investigate if it is compatible to basic home appliance. This project is tested on terrace house that the mailbox will be put outside within range of 500ft open space. Two main objectives of this project are to develop the innovation of smart mailbox and to implement the usage of solar panel as energy harvesting. It will be one of the modem technologies that help mankind to have a better life. Mailbox is a conventional way to send a letter while nowadays, everything is done via email. Therefore, upgrading a mailbox into a smart mailbox with some environmental friendly is a good start. This smart mailbox can help to notify the users when there is a load. Infrared sensor works when an obstacle comes and interfering the transmitting signal and green LED will lights up. Thus, radio frequency transmitter, (RF tx), will send signal wirelessly to the receiver that is to be put in the house. Receiver will then activate the red LED and buzzer will sound. This willbe off after the load has been taken.